Treatment results, including clinical prognostic factors and MGMT gene promoter methylation, in patients with glioblastoma multiforme in Warmia and Mazury Oncology Centre - Czeremszyńska, Beata; Bujko, Mateusz; Ibron, Grażyna; Onap-Karnak, Agnieszka; Nawrocki, Sergiusz (Contemporary Oncology/Współczesna Onkologia, 2011)
Aim of the study : To evaluate the results of survival of glioblastoma patients treated in Warmia and Mazury Oncology Centre in the years 2003-2008. Material and methods : Eighty-two patients (45 males; 37 females) with newly diagnosed histologically confirmed glioblastoma multiforme were treated. Thirty-eight patients were treated radically; this group includes 25 patients who had radiochemotherapy with temozolomide, and 13 patients treated only with radical radiotherapy. Forty-four patients had palliative radiotherapy. The tumour tissues of 23 patients were investigated for MGMT gene promoter methylation in the Department of Molecular Biology, Memorial Cancer Centre, Institute of Oncology, Warsaw. Results : The median overall survival (OS) of all patients was 10.5 months. The median OS for patients who were treated radically was 16.8 months and for patients who were treated palliatively it was 8.9 months. The median OS for patients treated with radiotherapy plus temozolomide was 27.4 months (for patients with methylated promoter of MGMT gene, 28 months; with unmethylated promoter, 26.5 months). One patient died of pulmonary and cerebral aspergillosis during radiochemotherapy. Leukoencephalopathy and cognitive disturbances were diagnosed in one 70-year-old patient after radiotherapy with temozolomide. Conclusions : The OS for patients treated with radiotherapy and temozolomide was longer than in the group treated only with radiotherapy. Differences were not observed in the median OS for patients with methylated and unmethylated promoter of MGMT gene, treated with radiotherapy plus temozolomide. The median OS for patients who had only radical radiotherapy is similar to the median OS for patients who had palliative radiotherapy.